Assessment of the spatial extent of permafrost in the Upper Indus Basin (UIB) - Hassan, Wasim; Jeelani, G.; Dimri, A. P.; Nüsser, Marcus (Journal of mountain science, 2023)
Climate change differentially influences the frozen ground, a major dynamic component of the cryosphere, on a local and regional scale. Under the warming climate with pronounced effects reported at higher altitudes, the characterization of the frozen ground is very important in the Upper Indus Basin (UIB), an important and critical region with respect to climate and hydro-glaciological dynamics. In this study, the efficiency and reliability of the surface frost number model are assessed in delineating the spatial extent of different classes of frozen ground in the region. The daily MODIS land surface temperature (LST) with ground surface temperature (GST) and surface geomorphological expressions as ground validation datasets are used jointly in efficiently determining the extent of different classes of frozen ground (continuous and discontinuous permafrost and seasonal frost). The LST and GST resonate with each other in the annual cycle of temperature variation, however, with mean annual LST exhibiting an offset (cold bias) of 5 to 7°C relative to mean GST. This study shows that the highest permafrost extent is observed in areas where the lowest thinning rates of glacier ice are reported and vice versa. The surface frost number model categorizes an area of 38% ± 3% and 15%± 3% in the UIB as permafrost and seasonal frost, respectively. Based on the altitude model, the lower limit of alpine permafrost is approximated at a mean altitude of 4919 ± 590 m a.s.l. in the UIB. The present study acts as preliminary work in the data sparse and inaccessible regions of the UIB in characterizing the frozen and unfrozen ground and may act as a promising input data source in glacio-hydro-meteorological models for the Himalaya and Karakoram. In addition, the study also underlines the consideration of this derelict cryospheric climatic variable in defining and accounting for the sustainable development of socio-economic systems through its intricate ramification on agricultural activity, landscape stability and infrastructure.
Veröffentlicht: 27. Juni 2023
Gesehen am 25.08.2023